Efeitos benéficos de probióticos no intestino de juvenis de tilápia-do-nilo - Mello, Hurzana de [UNESP]; Moraes, Julieta [UNESP]; Niza, Ines Garcia; Moraes, Flávio Ruas de [UNESP]; Ozório, Rodrigo; Shimada, Marina Tie [UNESP]; Filho Engracia, Jair [UNESP]; Claudiano, Gustavo [UNESP] (FapUNIFESP (SciELO), 2013)
The aim of this study was to evaluate the survival rate, the intestinal microbiota, the mucosal integrity, and the carcass quality of juvenile Nile Tilapia, Oreochromis niloticus, after 80 days being fed on a diet containing probiotic additive (Bacillus cereus 4.0×108 CFUg-1 and Bacillus subtilis 4.0×108 CFUg-1), at the ratio of 4g/kg of pelleted feed. The completely randomized design with two treatments was used: one control group and one group fed on the mentioned diet. The evaluation of survival rate, the intestinal microbiota analysis by microbiological culture, histomorphometrical analysis of intestinal mucosa and chemical analysis of carcass was performed. The results showed that tilapias from the treated group had higher relative survival rate (P<0.05) than the control group, higher number of colony-forming units (P<0.05) regarding intestinal colonization by B. cereus and B. subtilis, and higher rates of intestinal mucosal integrity (P<0.05), evaluated by histomorphometry. As for the latter, the group being fed on feed with probiotic additive was observed to have higher and larger villi, besides having a higher number of goblet cells than the control group. Concerning the carcass quality, the results showed that there was positive interference (P<0.05) of the probiotic on the treated group in comparison to the control group as in regard to levels of protein and ether extract. These results allow the inference that the supplementation with probiotic, as tested in this experiment, led to the intestinal colonization by beneficial bacteria and resulted in higher relative survival rate, decreased the mucosal desquamation and helped in the increase of the number of goblet cells.
Beneficial effects of probiotics on the intestine of juvenile Nile tilapia
Keywords: Bacillus cereus; Bacillus subtilis; Intestinal morphometry.; Nile tilapia; Oerochromis niloticus; Probiotics